Response of protein S100B to playing American football, lifting weights, and treadmill running - Rogatzki, M. J.; Keuler, S. A.; Harris, A. E.; Ringgenberg, S. W.; Breckenridge, R. E.; White, J. L.; Baker, J. S. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Objective: To determine if serum S100B increases similarly as a result of playing American football compared to exercise alone. Methods: Serum S100B was measured in division III collegiate football players before and after every home game during a single football season. Serum S100B was also measured before and after subjects walked on a treadmill for 30 minutes at a leisurely pace, ran on a treadmill while wearing and not wearing a football helmet at 6 mph for 8 minutes, and performed low-, moderate-, or high-intensity resistance exercise. Results: Serum S100B increased significantly (P < 0.05) when subjects played in a football game, ran on a treadmill, or performed moderate-intensity resistance exercise. Pre-game serum S100B did not accumulate throughout the football season in any of the players (P > 0.05). The increase in serum S100B during football games was moderately and significantly correlated with both the number of hits (R2 = 0.407) and the number of plays (R2 = 0.484) that each player experienced (P < 0.001). Post-game serum S100B was greater in football players who played more than 50 plays compared to those players who played <50 plays, subjects who exercised on a treadmill, or subjects performing resistance exercise (P < 0.05). Conclusion: It is unclear if the higher S100B concentration in football players playing at least 50 plays was caused by exercise or hits. Therefore, if serum S100B is to be used as a biomarker of impacts, and possible brain injury in sport, exercise time and intensity should be taken into account as confounding variables.